(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2020)
The application of financial market criteria to the art world has profoundly changed the reception of works of art. It is channelled through a private circuit of auction houses, galleries and collections, which monopolise the modalities of exhibition to the public and arbitrarily select works and artists, often conforming the taste of the spectators essentially to market criteria. This phenomenon is particularly important in the case of photography, which still remains, especially in some countries, on the fringes of the cultural system of museums and large exhibition spaces.